Pengembangan Halal Tourism di Malaysia: Studi Lapangan sebagai Pembelajaran Empiris bagi Penguatan Pariwisata Halal Indonesia - bunga indah zaletri; fahmi mardiah; nyiayu amrina rosyadah; ramadhanti viozani; belly rozana; alfa permata putra; asmar yulastri; yuliana yuliana; hendri azwar (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
The development of halal tourism has become a significant global trend, driven by the increasing number of Muslim tourists worldwide and the demand for Sharia-compliant tourism services. Malaysia is one of the countries that has successfully positioned itself as a leading halal-friendly destination globally. This article aims to analyze the concept, policies, and implementation of halal tourism in Malaysia based on a field study conducted by Master of Tourism students from Padang State University in November 2025. The method used was a descriptive qualitative approach through direct observation, academic discussions, and interviews with stakeholders at the Malaysia Tourism Information Center (MaTiC) and related institutions. The study results indicate that the success of Malaysian halal tourism is supported by strong synergy between the government, religious institutions, the tourism industry, and higher education institutions. In addition to its economic impact, halal tourism also contributes to strengthening cultural identity and community empowerment. This study is expected to serve as a reference for empirical learning and benchmarking for the development of halal tourism in Indonesia.